From Genetics to Clinical Implications: A Study of 675 Dutch Osteogenesis Imperfecta Patients - Silvia Storoni; Sara J. E. Verdonk; Lidiia Zhytnik; Gerard Pals; Sanne Treurniet; Mariet W. Elting; Ralph J. B. Sakkers; Joost G. van den Aardweg; Elisabeth M. W. Eekhoff; Dimitra Micha (Biomolecules, 2023)
Osteogenesis imperfecta (OI) is a heritable connective tissue disorder that causes bone fragility due to pathogenic variants in genes responsible for the synthesis of type I collagen. Efforts to classify the high clinical variability in OI led to the Sillence classification. However, this classification only partially takes into account extraskeletal manifestations and the high genetic variability. Little is known about the relation between genetic variants and phenotype as of yet. The aim of the study was to create a clinically relevant genetic stratification of a cohort of 675 Dutch OI patients based on their pathogenic variant types and to provide an overview of their respective medical care demands. The clinical records of 675 OI patients were extracted from the Amsterdam UMC Genome Database and matched with the records from Statistics Netherlands (CBS). The patients were categorized based on their harbored pathogenic variant. The information on hospital admissions, outpatient clinic visits, medication, and diagnosis-treatment combinations (DTCs) was compared between the variant groups. OI patients in the Netherlands appear to have a higher number of DTCs, outpatient clinic visits, and hospital admissions when compared to the general Dutch population. Furthermore, medication usage seems higher in the OI cohort in comparison to the general population. The patients with a COL1A1 or COL1A2 dominant negative missense non-glycine substitution appear to have a lower health care need compared to the other groups, and even lower than patients with COL1A1 or COL1A2 haploinsufficiency. It would be useful to include the variant type in addition to the Sillence classification when categorizing a patient’s phenotype.